Analisis Pengaruh Aplikasi Game Online Mobile Legend Di Kalangan Muda - Catherine.S.Lorentz Sitorus; Devi Patricia Hutagalung; Yuliana Sari (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Currently we see how the development of mobile phones has greatly influenced games or video games. Now with Android-equipped phones that can load more data stored on the phone, "games that previously could only be played offline are being developed, such as games on the Internet that can be played online indefinitely"¹, in this case. , games are also developed with the term "online games" which use data in their work. This continuously developing game then influences the lives of teenagers. The number of mobile devices is also increasing, this also has the influence of mobile legends which also increase the needs of children during the Covid pandemic, so the number of mobile phones also increases. In this magazine we will tell you about the effects of the Mobile Legends game. This research explains the influence of the Mobile Legends game on teenage behavior. This game is now widely spread among teenagers and has an impact on their socially unhealthy development in society.